Internment in the United Kingdom During the Twentieth Century and Its Links to the Evolution of Immigration Detention - Silverman, Stephanie J. (International Journal of Criminology and Sociology, 2014)
Immigration detention is cementing into a permanent aspect of border and immigration control in the United Kingdom. This article uses a historical examination of internment to contribute to a larger literature that unsettles the official record of detention policy as a natural development in an otherwise functioning immigration and border control bureaucracy. In so doing, I present an original overview of the First World War, Second World War, and Gulf War internments. My research findings demonstrate that wartime powers legislated in times of national distress have been repackaged as seemingly quotidian tools of immigration and asylum control. The results of this normalisation have included the reinforcement of a false logic of differentiation between citizens and threats, and between “good” and “bad” migrants; and an instrumentalisation of national insecurity to curtail the movements and basic rights of all individuals.